Minimal Access Surgery in Neonates - Ashrarur Rahman Mitul; Yogesh Kumar Sarin (EL-Med-Pub, 2017)
Despite the significant advancement of minimally invasive surgery (MIS) in the adults and even in pediatric population, its role as the standard of care in the neonates has not yet been established among the pediatric and neonatal surgeons universally. Lots of controversies still arise though several advanced centers in the world having very experienced surgeons performing MIS for neonatal surgical conditions with promising outcomes. The unique physiological characteristics of a neonate make MIS quiet a challenging subject among these tiny babies. We have tried to look into the recent literature on the issues related to the use of MIS for the surgical management of neonates.